Clinical trial capacity building in a pandemic—outcome of a rapid site readiness project in Latin America - Clemens, Sue Ann Costa; Gonzalez, Isabela; Sereni, Daniele; Clemens, Ralf (Frontiers in Public Health, 2024)
Background: Latin America (Latam) has contributed with large-scale trials, including in global vaccine development. However, because of fluctuating demand, many sites cannot maintain their infrastructure, and cannot engage as seen in the beginning of the COVID-19 pandemic. Therefore, the Bill and Melinda Gates Foundation (BMGF) launched in 2020 a clinical trial site readiness initiative. In Latam, 21 sites were qualified between August -November 2020. This survey aimed to evaluate clinical development performance measures prior to and after the project using a questionnaire (September 2022). Results: 20/21 prequalified sites initiated 156 clinical trials (140 COVID-19 vaccine/drug trials) in the 2 years since prequalification compared to 176 trials in the 5 years before, including 37,810 participants, 33,428 of which were included in COVID-19 programs. The number of enrolled subjects/site/per working day increased from 15 (range 1-35) before, to 63 (range 5-300) post capacity building. Dropout rate since award was 6.8%: 13 sites had dropout rates of ≤5%; 4 between >5% and ≤10%, and 3 >10%. Regulatory/Institutional Review Board approval timelines in none of the sites took longer than 3 months and was reduced from 60 (range 12-120) to 35 (range 5-90) days. The number of qualified/trained employees was 24 (range 6 -80) overall before and was increased to 88 (range 22-180) after the prequalification often by at risk hirings. Conclusions: The BMGF site readiness project contributed to the successful inclusion of 20/ 21 prequalified Latin American sites in the COVID-19 vaccine/drug development including vaccine efficacy trials, providing scientific evidence for rapid vaccine emergency use authorization. The project was widely accepted by sponsors, given the high number of different COVID-19 vaccines/drugs tested in Latam and the material increase in trials and subjects. Trial quality was high as evidenced by low dropout rates. For the 100 days ambition/ mission for vaccine availability in a potential new pandemic, it is essential that sufficient and well trained clinical trial sites are readily available. This can only be achieved if sites are maintained active not only in high income countries, but especially in low and middle-income countries through a constant flow of vaccine studies.